2005
DOI: 10.2337/diabetes.54.9.2812
|View full text |Cite
|
Sign up to set email alerts
|

INS VNTR Class Genotype and Indexes of Body Size and Obesity

Abstract: The relevance of the insulin gene (INS) variable number tandem repeat (VNTR) polymorphism to indexes of body size and adult obesity is inconclusive. Given the equivocal reports on the association between the VNTR class genotype at the insulin gene locus and indexes of body size and obesity, we assessed these associations in a series of cohort studies based on 7,999 middle-aged men and women. We found no convincing evidence that INS VNTR class genotype was associated with indexes of body size and adult obesity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The genotype distribution (AA 50.8%, AT 40.0%, and TT 9.2%) was similar to those found in previous studies and the frequency distribution did not deviate from the HardyWeinberg equilibrium (c 2 Z1.28, PO0.1) (8,11,19).…”
Section: Genotyping Ins Vntr Genesupporting
confidence: 70%
See 1 more Smart Citation
“…The genotype distribution (AA 50.8%, AT 40.0%, and TT 9.2%) was similar to those found in previous studies and the frequency distribution did not deviate from the HardyWeinberg equilibrium (c 2 Z1.28, PO0.1) (8,11,19).…”
Section: Genotyping Ins Vntr Genesupporting
confidence: 70%
“…It has also been suggested that this genotype is involved in childhood obesity and the development of metabolic syndrome (13,14), polycystic ovary syndrome (15), and type 2 diabetes in adulthood (16,17). Nevertheless, two large cohort studies were unable to demonstrate effects of INS VNTR on body composition or the risk of metabolic syndrome in adulthood (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…In a general population, other authors also did not support associations between INS VNTR and body composition in childhood [25][26][27][28].…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, class III is protective against diabetes mellitus type 1 (T1DM) and leads to an overexpression of insulin [19][20][21]. Thus, it may be responsible for obesity, IR, T2DM, and polycystic ovary syndrome (PCOS); however, the results regarding the influence of INS VNTR polymorphism on these disorders, both in the general population and in SGA individuals, are divergent [10,13,15,17,[22][23][24][25][26][27][28][29]. The aim of the study was to verify whether INS VNTR class III allele is associated with low birth weight in the Polish population and to assess the influence of this variant on the current body mass index (BMI) as well as on the metabolic and hormonal profile in prepubertal SGA children.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms of the INS gene have been found to be associated with obesity-related traits in children (Huede et al 2004;Ong et al 2004). However, there are also controversial results showing insignificant association of these polymorphisms with obesity in children or adults (Bouatia-Naji et al 2008;Sandhu et al 2005).…”
Section: Introductionmentioning
confidence: 99%